2020
DOI: 10.1002/esp.4790
|View full text |Cite
|
Sign up to set email alerts
|

Paired 10Be sampling of polished bedrock and erratic boulders to improve dating of glacial landforms: an example from the Western Alps

Abstract: Cosmogenic nuclide dating of glacial landforms may lead to ambiguous results for ice retreat histories. The persistence of significant cosmogenic concentrations inherited from previous exposure may increase the apparent exposure ages for polished bedrocks affected by limited erosion under ice and for erratic boulders transported by glaciers and previously exposed in high‐altitude rock walls. In contrast, transient burying by moraines, sediments and snow decreases the apparent exposure age. We propose a new sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Our results are also in agreement with previous dating of the glaciers position at the entrance of the Romanche and Arc valleys at 17.5 ka and 15 ka, respectively (Schwartz et al, 2017;Prud'homme et al, 2020), and between 17.5-16 ka in the Arve valley (Coutterand and Nicoud, 2005;Perret, 2014).…”
Section: Reconstruction Of Extent and Timing Of The Western French Al...supporting
confidence: 93%
See 1 more Smart Citation
“…Our results are also in agreement with previous dating of the glaciers position at the entrance of the Romanche and Arc valleys at 17.5 ka and 15 ka, respectively (Schwartz et al, 2017;Prud'homme et al, 2020), and between 17.5-16 ka in the Arve valley (Coutterand and Nicoud, 2005;Perret, 2014).…”
Section: Reconstruction Of Extent and Timing Of The Western French Al...supporting
confidence: 93%
“…The current lack of quantitative data for the LGM period raises the question of glacier paleogeography in the western French Alps foreland during this period. In the western French Alps, 10 Be surface-exposure dating spanning the late glacial and the Holocene period has only been applied on the inner valleys (Coutterand and Nicoud, 2005; Cossart et al, 2008, 2012; Perret, 2014; Wirsig et al, 2016; Le Roy et al, 2017; Schwartz et al, 2017; Protin, 2019; Protin et al, 2019; Prud'homme et al, 2020) and not in the foreland area.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the roches moutonnées at Kalgutinskii Rudnik could have been buried by till for some time, and by a thin snow cover. Prud'homme et al (2020) suggested that apparent exposure ages in erratic boulders and polished bedrock should be considered as maximum and minimum ages of glacial retreat, respectively. As we discarded the two oldest ages based on discordant 26 Al data, the remaining oldest age of c .…”
Section: Results and Interpretationmentioning
confidence: 99%
“…First, our approach relies on the assumption that bedrock surfaces have experienced a simple exposure history along the time period recorded by 10 Be concentrations, without pre-exposure or episodic coverage (i.e., non-erosive cold-based ice). Depth profiles of 10 Be measure-ments on glacially polished bedrocks in the western Alps, with apparent exposure ages of 10-20 ka, indicate that an inherited 10 Be concentration due to insufficient glacial erosion may persist and could lead to up to 9 % age overestimates (Prud'homme et al, 2020). Similarly, Wirsig et al (2016b) suggested potential but limited pre-LGM (less than a few ka overestimate) inheritance for some GELM samples.…”
Section: Interpretation Of Cosmogenic Nuclide Measurementsmentioning
confidence: 98%